Aspectos socioeconômicos, indicadores de qualidade e proposta de aproveitamento tecnológico do leite bovino produzido em unidades de produção de base familiar de Pato Branco - PR - Rosa, Arminda Almeida da (2012)
The dairy cattle has been established as an important socioeconomic activity in family farms across the country. Such activity has been considered as warranty of survival of families in the country region promoting their social reproduction. As one of the main food available for people, the production of milk has been demanding technologies to guarantee its quality under physicochemical and microbiological aspects, among others. Within this context, this research presents a socioeconomic approach of bovine milk farmers who live in a community in the interior of Pato Branco district, in the southwest area of Paraná state, with the intention of understanding the families’ characteristics, specific aspects in the production of milk, and what this activity has represented concerning socioeconomic terms for these families, as well as the quality of the produced milk. The present study carried out three work phases. Initially, a diagnosis of 26 families of the Independence community was accomplished, with the intention of obtaining information regarding their social and economic reality, and important aspects regarding the development of dairy activity. In the second phase, samples of milk were collected in the properties with the objective of evaluating its physicochemical, microbiological quality, as well as in relation to the presence of residues of medicines for veterinary use, antibiotic residues and aflatoxins. Water used in the dairy was also collected to evaluate its microbiological quality. The third phase involved the elaboration of handmade cheeses similar to Boursin, as a proposal of technological use of the milk, together with a research of sensorial evaluation and intention of purchase of the developed products. The researched community has potential for the dairy cattle activity, presenting high dairy productivity. Regarding the quality of the milk, the research demonstrated needs of improvements in the handling and hygiene concerning the milking of the animals, among other factors related to the use of the available technological knowledge. The development of a differentiated product was possible, which can be considered as an alternative of income and rescue of the community's culture in the production of cheeses, consisting of a proposal of economic and social development for the family based production units.